Neder-landtsche gedenck-clanck - Valerius, Adriaan -1625; Meertens, P. J. (Amsterdam Facsimile Uitgaven Nederland N.V., 1968)
Songs used to be much more important than they are today. You didn't need to be able to read to sing along; they were easy to remember and spread. They could convey mood and atmosphere, tell stories, bring news, and spread propaganda. The 76 songs in Adriaen Valerius' Nederlandtsche Gedenck-clanck (Sounds in memory of important Dutch events, 1626) did all of that. They were written to well-known melodies and told of the changing circumstances of anger, despair, and victory in the war of independence that had been waged against Spain since 1568. They promoted the Dutch cause, especially the Calvinist cause.The book was compiled by Adriaen Valerius, a notary from Veere in Zeeland. He had already contributed to a Zeeland poetry collection, Zeevsche Nagetgael (1623), and was a member of the local chamber of rhetoric De Witte Lelie en Blauwe Acolye, also known as Missus Scholieren. Valerius compiled a chronological overview with reports and stories about the war and wrote the songs as a link between the prose pieces. He died in 1625 before he could publish his work; his son published it a year later. It was a fairly expensive book with a varied layout, illustrations, prints, and musical notation for the songs. It was clearly intended for an audience that was willing to pay for the history of the Netherlands and that continued to support the Revolt. (Translated with DeepL.com)
Kortelick openbarende de voornaemste geschiedenissen van de seventhien Nederlandsche Provintien, 't sederden aenvang der inlandsche beroerten ende troublen, tot den jare 1625
Keywords: 17th Century (1601-1700); Song; History; Netherlands